More than just emotional intelligence online: introducing “digital emotional intelligence” - Audrin, Catherine; Audrin, Bertrand (Frontiers in Psychology, 2023)
The ubiquitous nature of emotional intelligence, as a central theme in every aspect of our lives—be it at work, school, or home—coupled with the growing prevalence of digital interactions, makes it fundamental to develop our understanding of emotional intelligence in a digital world. However, the digital world represents more than just a contextual factor to consider, as interactions in digital environments require digital competence. The objective of this paper is to conceptualize “digital emotional intelligence” as the integration of both emotional intelligence and digital competence. The model we propose posits that trait emotional intelligence predicts attitudes towards digital competence, while digital ability emotional intelligence is predicted by digital competence skills and digital competence knowledge. Using a self-reported questionnaire on 503 respondents, a structural equation model highlights a positive relationship between trait emotional intelligence and attitudes towards digital competence.